Living in the lab: an analysis of the work in eight living laboratories set up in care homes for technology innovation. Issue 1 (2nd January 2017) - Kanstrup, Anne Marie
Abstract: Examinations of living labs are scarce even though the approach is increasingly used as an opportunity to bring design activities into real-life use context and consequently facilitate cooperations between designers and users in future technology innovation. Furthermore, examinations of living labs that focus on the people living in the labs do not exist. This paper presents a study of eight living labs set up in care homes for innovation in health technologies and focuses on the work carried out by care workers, service staff, residents and management, i.e. people living and working in the labs. The analysis reveals a comprehensive system of work carried out by people living and working in the labs and identifies that linking the lab-work-system to the ongoing existing work-system is a major challenge. The study demonstrates that the work of people living and working in the labs is critical to the success of living labs and recommends greater focus on work balance, user gains and collaborative innovation in living lab theories and methods.